Interleukin-1 as a therapeutic target in gout. Issue 2 (March 2015) - Dumusc, Alexandre; So, Alexander
<x xml:space="preserve">Abstract</x> Purpose of review To give an overview of current evidence for interleukin (IL)-1 blockade in the management of gout. Recent findings Three IL-1 blockers are currently available for clinical use: anakinra, rilonacept and canakinumab. Recent studies have focused on drugs with a long half-life: rilonacept and canakinumab. For treatment of acute gouty arthritis, three randomized controlled trials (RCTs) showed efficacy of canakinumab with some safety concerns and one RCT failed to show efficacy of rilonacept. For prevention of gout flare when starting uric acid lowering therapy (ULT), four RCTs showed efficacy of rilonacept and one RCT showed efficacy of canakinumab. Summary There is sufficient evidence supporting the use of IL-1 blockers for treatment of acute gouty arthritis or for prevention of gout flares when starting ULT in selected patients, with contraindications or intolerance to conventional therapy. More data are needed to assess safety and to specify their use in routine practice.